Factors affecting retention in the Philippine National Rural Physician Deployment Program from 2012 to 2019: a mixed methods study - Erika Louise L. Flores; Edric Matthew R. Manahan; Miguel Paulo B. Lacanilao; Isabella Ma. Beatriz T. Ladaw; Mico Martin B. Mallillin; Nikolai Thadeus Q. Mappatao; Juan Alfonso Leonardia; Veincent Christian F. Pepito (BMC, 2021)
Abstract Background To address the maldistribution of healthcare providers and the shortage of physicians in geographically isolated and disadvantaged areas of the Philippines, the Philippine National Rural Physician Deployment Program, or more commonly known as the Doctors to the Barrios (DTTB) program was established in 1993. However, as of 2011, only 18% of the DTTBs chose to stay in their assigned municipalities after their two-year deployment, termed retention. This study aims to identify the individual, local, work, national, and international factors affecting the retention of DTTBs in their assigned communities after their two-year deployment. Methods A descriptive, mixed-methods, explanatory design was used. For the quantitative part, the modified and updated Stayers Questionnaire was given to all current DTTBs present in a Continuing Medical Education session in the Development Academy of the Philippines. Descriptive statistics were then presented. For the qualitative part, individual, semi-structured key informant interviews were conducted in-person or via phone with current and alumni DTTBs from 2012 to 2019. Proceedings of the interviews were transcribed, translated, and analyzed thematically. Results 102 current DTTBs participated in the quantitative part of our study, while 10 current and former DTTBs participated in the interviews. Demographic factors and location, personal beliefs, well-being, friends and family dynamics, and perceptions about work were the individual factors identified to affect retention. Social working conditions, career development, and infrastructure, medical equipment, and supplies were among the work factors identified to affect retention. Geography, living conditions, local social needs, and technology were among the local factors identified to affect retention. Compensation, the recently signed Universal Healthcare Law, and Safety and Security were identified as national factors that could affect retention. International factors did not seem to discourage DTTBs from staying in their communities. Conclusions A host of individual, work-related, local, national, and international factors influence the DTTB's decision to be retained in different, complex, interconnected, and dynamic ways. We also identified implementation issues in the DTTB program and suggested interventions to encourage retention.